The influence factors of neonatal respiratory distress syndrome in Southern China: a case-control study. (18th May 2020) - Ye, Wei; Zhang, Tongqiang; Shu, Yang; Fang, Chengzhi; Xie, Lili; Peng, Kaiwei; Liu, Chunmei
Abstract: Objective: To explore the relevant influencing factors of neonatal respiratory distress syndrome (NRDS) in southern China and provide scientific basis for improving the quality of life for neonates. Methods: A retrospective analysis of 320 cases with NRDS neonates admitted from January 2015 to December 2017 in a neonatal department of a Maternal and Child Health Hospital in South China was conducted. Three hundred twenty non-NRDS patients admitted to the same hospital during the same period were also included as control. The basic characteristics were compared and the risk and protective factors for NRDS were evaluated by logistic regression analysis. Results: Univariate analysis showed that the difference in age, gestational age, fetal sex, mode of delivery, asphyxia, intrauterine distress, and gestational diabetes in the case group and the control group were significantly different ( p  < .05). The multivariate logistic regression analysis revealed that the age of pregnant women (OR ± 1.539, 95% CI ± 1.427–1.660), intrauterine distress (OR ± 2.427, 95% CI ± 1.079–5.458), and gestational diabetes (OR ± 2.881, 95% CI ± 1.271–6.532) were independent risk factors for NRDS. Meanwhile, gestational age (OR ± 0.588, 95% CI ± 0.508–0.681) was an independent protective factor for NRDS. Conclusions: The age of pregnant women, intrauterine distress, and gestational diabetes can increase the risk of NRDS, while long gestational age can reduce the risk of NRDS. Early detection, early diagnosis and early treatment of children with NRDS have achieved the purpose of improving the quality of life of children.